A Study Of Factors Contribute To Account Executives Performance In Telekom Malaysia - Abu Samah, Ab. Razak (2000)
The human resource practices and the attitudes and behaviours of the account executives(AEs) as contact employees can influence customers' perception of the service. This study examined the impact of internal service quality (employee committment, organis